Dukungan Keluarga pada Lansia Program Keluarga Harapan - Cut Ita Zahara; Yara Andita Anastasya (Program Studi Psikologi Fakultas Kedokteran Universitas Malikussaleh, 2020)
This study aims to obtain an overview and identify forms of family support for the elderly FamilyHopeProgram. The approach taken is a qualitative approach with purposeful sampling technique with the criteria being the elderly in the Family Hope Program, aged 60 to 70 years, able to communicate well, willing to be the subject of research and domiciled in Dewantara, North Aceh District. The number of subjects in this study were 5 people. The results showed that four out of five research subjects stated that the family did not provide maximum support such as paying less attention to the state of health, having their own activities, and not helping financially.